Advances in Architectural Geometry 2023 - Dörfler, Kathrin; Knippers, Jan; Menges, Achim; Parascho, Stefana; Pottmann, Helmut; Wortmann, Thomas (De Gruyter STEM, 2023)
Modern geometric computing increasingly plays a role in modeling environments and processing sensing information, providing a variety of tools for the efficient design, analysis, and manufacturing of complex shapes. The research area of architectural geometry (AG) has emerged at the common border of architecture, applied geometry, computational design, mathematics, and manufacturing. This book presents the state of the art of research in AG.